Global validation of ENVISAT ozone profiles using lidar measurements - van Gijsel, J. A. E.; Swart, D. P. J.; Baray, J. L.; Claude, H.; Fehr, T.; von der Gathen, P.; Godin Beekmann, S.; Hansen, G. H.; Leblanc, T.; McDermid, I. S.; Meijer, Y. J.; Nakane, H.; et al. (International Journal of Remote Sensing)
Satellite sensors provide global measurements of ozone concentration that can be used to study the effects of the implementation of the Montreal Protocol. However, a key issue in deriving long-term ozone trends from successive satellite instruments is inter-comparability. Ground-based measurements offer continuous time series, but only at a few locations. The combination of ground-based measurements with satellite data is therefore an effective means to evaluate satellite instrument inter-comparability. In this study, we present validation results of ozone profiles from three atmospheric sensors onboard ENVISAT by comparison with lidar measurements. Results for the SCIAMACHY ozone profiles (version 3.01) show reasonable agreement with ground-based measurements (0 to -20%). The MIPAS full-resolution (version 4.61) dataset has good agreement with lidar (0 to 10%), whereas a small positive bias (up to 20%) was found for the MIPAS reduced-resolution prototype data. GOMOS dark-limb data (version 5.00) agree very well (0 ± 5%) with the correlative data, but underestimate ozone concentration at the polar regions. Fil: van Gijsel, J. A. E. National Institute for Public Health and the Environment; Países Bajos Fil: Swart, D. P. J. National Institute for Public Health and the Environment; Países Bajos Fil: Baray, J. L. Université de la Reunión; Francia Fil: Claude, H. Meteorological Observatory Hohenpeissenberg; Alemania Fil: Fehr, T. European Space Agency; Italia Fil: von der Gathen, P. Alfred Wegener Institute; Alemania Fil: Godin Beekmann, S. Centre National de la Recherche Scientifique; Francia Fil: Hansen, G. H. Norwegian Air Research Institute; Noruega Fil: Leblanc, T. National Aeronautics and Space Administration; Estados Unidos Fil: McDermid, I. S. National Aeronautics and Space Administration; Estados Unidos Fil: Meijer, Y. J. European Space Agency; Italia Fil: Nakane, H. National Institute for Environmental Studies; Japón Fil: Quel, Eduardo Jaime. Consejo Nacional de Investigaciones ...